(untitled) (World Economics and Finance Bulletin, 2024)
In recent decades, there has been a swift digital transformation leading to significant, and occasionally even pivotal, developments in the global economy, business, and society. Whether estimations of Gross Domestic Product (GDP) still offer accurate indicators of development in a digitalized economy has turned into a contentious issue. The characteristics of the digital economy have significant ramifications for measuring GDP, productivity, and family well-being in the retail industry, as well as throughout the economy’s service sectors. As a fresh inspiration for economic globalization, the growth of the digital economy presents both opportunities and challenges for further advancement. The productivity paradox should be acknowledged in the digital economy, recognizing that GDP numbers have limitations when it comes to tracking the sector’s progress. In light of the declining productivity and the continued growth of the digital economy, this study offers fresh insights into the identification of disruptive business models driven by digital solutions. This paper’s contribution is to empirically evaluate how the digital economy affects GDP using data from the global economy. Data and information from many sources were gathered for this research through a literature survey, for the gathering of GDP and digital economy statistics. The data sources included specific data from the US BEA, OECD, ADB, APEC, and IMF